Predictor of Women's Handball Athlete Fitness Level Malang City Through Fat-Free Mass Measurement - Yusuf, Havid; Nidomuddin, Muhammad; Pamungkas, Hari (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2023)
Athletes are individuals who focus on the world of sports according to their sport. Handball requires athletes to perform repetitive high-intensity activities in running, attacking and defending tactics, interspersed with periods of low intensity and/or rest. Physical fitness as a benchmark for coaches to determine what athletes need to be prepared for. There are several elements that can be seen by changes in the athlete's physical condition through anthropometric characteristics, for example, fat-free mass. The main objective of this study was to assess changes in anthropometric body composition, namely, lean body mass in female handball athletes within 2 months and ensure that this predictor can contribute to sports success. The samples involved were 12 female handball athletes. The instrument used to measure body composition is the Seca mBCA 514 Medical Body Composition Analyzer. The results of this study were that lean body mass increased from the first month to the second month with p = 0.01. The average pre-test fat-free mass in women's handball athletes was 39.92 kg, while the post-test fat-free mass in women's handball athletes was 40.67 kg. The average difference between the two is 0.75 kg. This increase in fat-free mass is in accordance with the theory that has been explained, that the greater the fat-free mass in an individual, the greater the quantity of muscle mass as well. This study shows data through pre-test-treatment-post test treatment on female handball athletes. Changes in anthropometry, body composition, and physical fitness are some of the predictors of successful sports achievements in a competition.